Determinación de valores hematimétricos de perros clinicamente sanos en la ciudad de Quito - Donoso Proaño, Luis Fernando (2013)
The present study aims to determine complete blood counts (CDC) reference values in clinically healthy dogs located in Quito, Pichincha. The research was conducted at the Specialization Veterinary Teaching Hospital of Quito (USFQ) . The general objective of the investigations was: to determine the overall CDC deficiency of the region in order to correct this parameters. The specific objectives were to: 1.Determine the normal CDC values of clinically healthy dogs of the city of Quito. 2. Compare the CDC values in the statistical sample with the current reference values. 3. Provide professional veterinarians a framework appropriate to the particular characteristics of region, thus sparing the consultation of literature generated in other countries. The CDC values were determined from 120 dogs. The following variables were assessed: Age, race and sex. Age was documented as: Puppy (birth-1 year), Adult (1-8 years) and Elderly (over 8 years). Race was evaluated as: Small ( 0-5 kg), Medium (5-20 kg), Large (21-40 kg) and Giant (over 40 kg). The quantitative variable of Sex was documented as: Male and Female. The blood samples were obtain from the cephalic vein, the most common technique.For the statistical analysis of the data the program Statistical Package for Social Sciences (SPSS) was used. The data from 120 animals was entered in ther program and its distribution was based on the functional analysis of the variables: sex, age and race. The next hematimetric values were also entered: hematocrit, hemoglobin, erythrocytes, platelets, leukocytes, lymphocytes, monocytes, eosinophils. The hypotheses were: H0: There is no difference between the mean CDC values from quito´s dogs and the mean CDC values given by the laboratory, which were interpreted by international rates. H1: there is a differences between the mean CDC values of the dogs from the city of Machala with the mean CDC values given by the laboratory, which were also interpreted by international rates. The 5% significance level = 0.05, was applied to the statistical t-test and p-value estimate.The reference values were found by using the classical method that was calculated based on the mean value +/- twice the standard deviation (x 2s). The hematimetric indexes were: males hematocrit levels with a mean value of 0.455, standard deviation of 0.060 and reference intervals ranging from 0.34 to 0.58. In the case of females, the mean value was 0.47 with a standard deviation of 0.057 and reference ranges from 0.34 to 0.58%. The values of hemoglobin in the case of males, the mean value was of 154.51, with a standard deviation of 21.032; with the reference intervals ranging from 112.44 to 196.57. Females showed an average of 155.13, with a standard deviation of 18.91 and established references documented ranges from 117.3 to 193. The erythrocyte count in males was an average of 6.84, with a standard deviation of 0.84. with this data a range could be established ranging from 5.15 to 8.53. Females mean values dropped to 6.73, with a standard deviation of 0.92 and the reference ranges were 5.0 to 9; With regard to platelets males showed an average of 314; with a 54.4 standard deviation and ranges from 205 to 423. Females had a mean of 345,5 and a standard deviation of 49,8; the reference ranges ranged from 245.9 to 445. On average, leukocytes in males were 10.88, with a standard deviation of 3.6, and reference ranges from 3.7 to 18. Females has an average of 9.6, with the standard deviation of 3.5, and reference ranges from 2.49 to 16.6.Analyzing lymphocytes, the male had an average of 16.5, with a standard deviation of 7.8, and range references 94-32. Females showed a mean of 5.4, with a standard deviation of 3.8, and reference intervals 1-27; Monocytes average in females was 5,43, with a the standard deviation of 3.8, and reference ranges from -2.14 to 13. The males exhibited an average of 4.53, with a standard deviation of 2.9, and reference ranges from -1.3 to 10.3; Finally, eosinophils, with an average of 3.03 in males, a standard deviation 5.7, and reference ranges from -8.4 to 14. Females had a mean of 1.40, with a standard deviation of 2.09, and reference ranges from -2.8 to 5.6.